Social Work Education during the Covid-19 Pandemic: Lessons Learned for Programming and Practice - Dana Alonzo; Pinar Zubaroglu-Ioannides; Gulcan Urhan; Mashura Akilova (International Journal of School Social Work, 2024)
Background: In response to the COVID-19 pandemic, remote learning was rapidly implemented across schools of social work. This study examines the student perspective of online learning during the pandemic including the challenges faced from the unanticipated switch to remote learning and any benefits gleaned from remote learning. Method: We conducted an online survey of social work students using Qualtrics. Surveys were delivered electronically to schools of social work in Turkey using convenience sampling. Qualitative data was analyzed using content analysis and quantitative data was analyzed using SPSS. Results: The majority of the participants in our study (76.5 %) ranked their online education experience as fair (3 out of 5), reporting the most benefits of remote learning related to the academic domain and the greatest challenges related to the domain. Bi-variate analyses showed those over age 22 reported more experience of stress and anxiety (p=0.20), and those younger than 22 years have greater difficulty with staying on a screen for extended periods (p=0.40). A lack of digital learning materials (p=0.28) and stable internet connection ( p=0.49), were also noted as key challenges. Conclusion: The need for flexibility in teaching practices and course requirements and increased attention to mental health are important for ensuring an effective online learning experience. Future contingency plans should account for the need for interactive technology in online social work classrooms that facilitate the relationships, engagement and sense of belonging that are such a critical component of social education.
Keywords: social work; online education; pandemic; Covid-19